EVALUATING THE ACCURACY OF THE NEUTROPHIL-TO-LYMPHOCYTE RATIO IN DIAGNOSING ACUTE APPENDICITIS - Muhammad Adnan Rashid,; Javed, Hamza; Fida Muhammad,; Fatima Asad,; Dania Dawood,; Easha Jadoon,; Gulalay Shamal,; Amir Moavia, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Acute Appendicitis, a surgical emergency, is one of the most common causes of acute abdomen. Its’ immediate diagnosis and surgery are of immense significance for the disease itself and its surgery carries a potential risk of morbidity and mortality. The goal of this study was to find out the role of Neutrophils to Lymphocyte Ratio (NLR) in making a confident diagnosis of acute appendicitis in a facility limited setup. Methods: It is a cross-sectional validation study on 100 patients admitted to the surgical wards of Ayub Teaching Hospital Abbottabad, with suspicion of Acute Appendicitis (AA), who subsequently underwent open appendectomy. Data were collected regarding the demography (name, age, gender) of the patient, physical examination, clinical presentations, and investigations including the complete blood count, from which the NLR value was calculated. Data was also collected regarding the histopathology examination of the appendix. Results: The sensitivity was 70.65% while the specificity was 87.5% and accuracy was 72%. Positive Predictive Value (PPV) was 98.4% and NPV was 20.6%. Conclusion: There is a strong correlation between NLR value and Acute Appendicitis. According to the results of our study, NLR ≥ 2.5 seems to be a reliable parameter to obtain a more certain diagnosis of Acute Appendicitis.